Structural evolution and sodium storage properties of γ-ray irradiated hard carbon - SONG Xiaohui; SHI Haiting; WANG Shuo; GAO Pan; XU Zhiwei (Fushe yanjiu yu fushe gongyi xuebao, 2024)
In this study, self-doping defects were introduced to optimize the interlayer spacing and pore structure of hard carbon by γ-ray irradiation. The effects of the absorbed dose on the interlayer spacing, internal defects, and disordered structure of hard carbon were investigated through scanning electron microscopy (SEM), X-ray diffraction (XRD), Raman spectroscopy, and isothermal nitrogen adsorption/desorption. The electrochemical properties were investigated using the constant current charge-discharge. The results showed that the surface crystallinity and disordered structure of hard carbon increased with the absorbed dose. Moreover, the electrochemical properties of hard carbon were clearly improved. At a dose of 140 kGy, hard carbon presented a high specific surface area of 425.343 m2/g and provided a sodium storage capacity of 300 mAh/g at 30 mA/g; the high current density capacity remained at 195 mAh/g at 1 A/g, suggesting that the electrode capacity increased three-fold. Excellent stability was also maintained during high-rate charge-discharge. This work provides new approaches and ideas for the design of advanced nanomaterials and defect engineering applications in the field of energy storage.